Relationship of Flat Foot and Plantar Fascia Thickness in Medical Students of Pelita Harapan University - Taniwangsa, Livia; M.T. Siahaan, Yusak (Medicinus, 2020)
Background : Plantar fascia plays significant role in supporting the height and structure of Medial Longitudinal Arch (MLA). In flat foot, the MLA is depressed. There is thickening of plantar fascia reported in cases of plantar fasciitis in subjects with flat foot. Therefore, research needs to be done to investigate the relation between flat foot and plantar fascia thickness.Aim:  To understand the relationship between flat foot and plantar fascia thickness among medical students of Pelita Harapan University.Methods : This study was conducted using cross-sectional method with sampling method of non-random consecutive sampling. Data was collected through examinations performed and adjustments are made using inclusion and exclusion criteria. Flat foot was determined using navicular drop test and plantar fascia thickness was assessed using ultrasonography measurement. Results were analyzed using SPSS 22.0 and statistically tested using Spearman’s rho test.Result : The analysis of the relationship between flat foot and plantar fascia thickness showed positive correlation with correlation coefficient of 0.634 on the right foot and 0.443 on the left.Conclusion : There is moderate and strong positive relationship between flat foot and plantar fascia thickness among medical students of Pelita Harapan University.